What drives support for social distancing? Pandemic politics, securitization, and crisis management in Britain. Issue 4 (21st November 2021) - Karyotis, Georgios; Connolly, John; Collignon, Sofía; Judge, Andrew; Makropoulos, Iakovos; Rüdig, Wolfgang; Skleparis, Dimitris
Abstract: Support for social distancing measures was, globally, high at the early stages of the COVID-19 pandemic but increasingly came under pressure. Focusing on the UK, this article provides a rigorous exploration of the drivers of public support for social distancing at their formative stage, via mixed methods. Synthesizing insights from crisis management and securitization theory, thematic analysis is employed to map the main frames promoted by the government and other actors on the nature/severity, blame/responsibility, and appropriate response to the pandemic, which 'follows the science'. The impact of these on public attitudes is examined via a series of regression analyses, drawing on a representative survey of the UK population (n = 2100). Findings challenge the prevailing understanding that support for measures is driven by personal health considerations, socio-economic circumstances, and political influences. Instead, crisis framing dynamics, which the government is well-positioned to dominate, have the greatest impact on driving public attitudes.